1991
DOI: 10.1002/eji.1830210625
|View full text |Cite
|
Sign up to set email alerts
|

The mouse IgH 3′‐enhancer

Abstract: A lymphoid-specific transcription enhancer element has recently been identified at the far 3' end of the rat immunoglobulin heavy chain (IgH) locus. Sequence analysis presented here reveals that this enhancer is flanked by a 350-bp invert repeat, giving a structure reminiscent of a transposable element. We therefore screened for the equivalent enhancer in the mouse to determine whether its presence was conserved during evolution. A mouse homologue was indeed identified and is located 16 kb downstream of the C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 23 publications
6
98
0
Order By: Relevance
“…The discovery of an enhancer (hs1,2) downstream of the rodent IgH constant region genes was the result of a search for regulatory sequences that could explain IgH gene expression in E -deficient, Ig-secreting cells (32)(33)(34). Chromosome translocations that juxtaposed the oncogene c-myc with the 3Ј end of the Igh locus, resulting in a promoter shift and deregulated c-myc expression, also compelled this search (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of an enhancer (hs1,2) downstream of the rodent IgH constant region genes was the result of a search for regulatory sequences that could explain IgH gene expression in E -deficient, Ig-secreting cells (32)(33)(34). Chromosome translocations that juxtaposed the oncogene c-myc with the 3Ј end of the Igh locus, resulting in a promoter shift and deregulated c-myc expression, also compelled this search (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the IgA + B cell with the Ighm/c-myc exchange may already have completed plasmacytic di erentiation, while the IgM + B cell with the Igha/cmyc exchange may still remain at the development stage of a mature lymphocyte. Ongoing clonal diversi®cation generating a continuum of aberrant, di erentiating B cells harboring the t(12;15) at various stages of`remodeling' may thus characterize plasmacytoma development in BALB/c mice that are located 3' of Ca (Pettersson et al, 1990;Dariavach et al, 1991;Matthias and Baltimore, 1993;Madisen and Groudine, 1994;Michaelson et al, 1995). However, 3'-c-myc enhancers have not been identi®ed thus far, and the two candidate enhancer elements that were recently found in a molecular analysis of the 30 kbp downstream region of the human c-myc gene (Mautner et al, 1995) have been shown in subsequent studies to be insu cient to upregulate c-myc expression in vivo (Mautner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same general region is implicated as an origin of Igh DNA replication in MEL, as inferred from the work of Brown et al (4). The ϳ40-kb region immediately downstream of C␣ that spans the 3Ј Igh regulatory region, as mentioned in the introduction, has only recently been fully described (8,21,24,25,27,29,31). In order to clone sequences downstream of the regulatory region, we screened a 129-OLA phage library (Materials and Methods) with probe 0.7 Hc/E from the extreme 3Ј end of the 23-kb EcoRI fragment (Fig.…”
Section: Isolation Of Sequences Downstream Of the Igh 3 Regulatory Rementioning
confidence: 84%
“…We and others have described a complex 3Ј regulatory region spanning 40 kb downstream of C␣. Four B-cell-specific enhancers, each of which is associated with DNase I hypersensitivity, have been identified in the 3Ј regulatory region (8,21,24,25,27,29,31), as shown in Fig. 1.…”
mentioning
confidence: 99%